Requirements of German logistics companies for charging battery-electric trucks: Results of a combined survey and interview study - Aline Scherrer; Marvin Helferich; Daniel Speth; Steffen Link (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2024)
The electrification of heavy-duty road transport and logistics operations presents a significant challenge in meeting CO2 reduction goals. Despite increasing attention to battery-electric trucks (BETs) as a primary strategy among manufacturers, their market share remains limited in Europe and Germany. Logistics companies, as primary users of heavy-duty vehicles (HDVs), face various challenges such as tight budgets, time constraints, and diverse operational needs, which significantly influence the adoption of BETs. Previous studies have identified general key obstacles including purchase price, charging infrastructure availability, vehicle range, payload limitations, total ownership costs, technology perception, and operational adaptations. However, further investigation is needed to understand company-specific requirements and operations of different logistics segments, especially regarding charging infrastructure limitations. This study employs a mixed methods approach to explore logistic companies' perspectives on charging infrastructure and BET adoption. A survey of German logistics companies, followed by semi-structured interviews, provides insights into current fleet operations, attitudes towards BETs, and motivations for electrification. The survey findings highlight the diverse vehicle types and driving profiles within logistics fleets, with a focus on identifying most readily electrifiable trucks (RETs) based on usage patterns. Analyses of survey data, conducted mainly through descriptive statistics, reveal the complexities of trip planning, on-site charging infrastructure, and public charging implications for BET adoption. Interviews with selected respondents further delve into company characteristics, daily operations, usage intentions, and barriers related to BET adoption and charging infrastructure. The results indicate that the regularity and plannability of trips differs across tour types and distances, impacting the potential integration of BETs in operations. Tour regularity varies greatly for individual vehicles beyond urban applications, impacting the flexibility needed for charging. The longest coherent parking time is predominantly spent on private property, with home depots being more important than client locations. Challenges for establishing and using charging infrastructure include the lack of medium voltage grid connections for fast charging at home depots, heterogeneous conditions at client waiting and loading areas, and uncertainties regarding the availability and operational integration of public charging infrastructure. Companies in the sample operating a large number of RETs also hold the most positive attitudes towards BETs, with some already deploying such vehicles. Factors influencing the engagement of logistics companies in fleet electrification include personal motivations, growing customer demands for decarbonised transport, and regulatory requirements. Methodological limitations of the study include a bias towards large fleets in the sample, limiting extrapolation of findings to the broader market. Key recommendations include addressing barriers to at-home and client location charging to support fleet electrification efforts effectively. The findings provide insights into the operational considerations and motivations driving charging infrastructure deployment and fleet electrification. Furthermore, they offer implications for policymakers and industry stakeholders aiming to accelerate the transition to electric HDVs.
Keywords: 330; Battery-electric trucks; Charging infrastructure; Logistics; Heavy-duty vehicles; Decarbonization; User requirements; MCS; Megawatt charging; Alternative fuels; Zero-emission trucks; Mixed methods; Survey; Interviews